Indefinite stuckness: Listening in a time of hyper-incarceration and border entrapment. (July 2020) - Russell, Emma K; Rae, Maria
New technologies for recording, reproducing, and disseminating sound are increasingly accessible and provide important opportunities for listening to accounts of confinement. Through a politics and practice of 'earwitnessing detention', this article explores experiential patterns and distinctions between immigration detention and imprisonment. By 'tuning in' to radio and podcasting emerging from and through carceral spaces, we argue that both detained asylum seekers and Aboriginal prisoners in Australia narrate an experience of 'indefinite stuckness'. Indefinite stuckness is an existential condition within a carceral continuum that is both spatial and temporal, and characterised by massive racial inequalities. For detained asylum seekers, indefinite stuckness manifests in the absence of a set release date, whereas for Aboriginal prisoners, it is a cycle of criminalisation and re-incarceration in the colony. This important distinction shapes how detention is represented: as torturous and abusive, or as an opportunity for respite from the 'chaos' outside. Linking these sometimes-divergent accounts of confinement are themes of friendship and community as forms of survival and resistance to the abjection that frequently accompanies indefinite stuckness.